Internationalization of Higher Education: An Analysis on The Requiremens and Challenges - Lim, Lay Beng, Aris (2007)
This dissertation analyses the requirements and challenges pertain to the latest phenomena of internationalization of higher education. The knowledge-base economy is driven by the internationalization and globalization of the global economy. Internationalization of higher education is very much in respond to the impact of globalization of economy. This development in higher education is addressed by analyzing the requirements and challenges of higher education institutions face to set up branch campuses overseas. The first part of this study focuses the fundamental concept of internationalization and globalization. Then explains the why international is required in this emerging economy and the importance of government's role in the higher education sector. It also highlights the impacts from the mobility of students study overseas that create a missification in transnational education. It identifies that in order to maintain the quality and assurance in higher education, government's intervention is critical. For institutions venturing overseas, it is important for them to consider the challenges and success factors. The location of a branch campus would be one of the fundamental strategies. This study explains how GATS implementation impacts on internationalization of higher education. Lastly, it further analyzes higher education in Asia and specially highlighted Singapore and Malaysia and the recently sudden closure of UNSW Singapore campus. In conclusion, this report highlights that internationalization of higher education is critical to the knowledge-base economy.